2018
DOI: 10.1186/s41601-018-0087-z
|View full text |Cite
|
Sign up to set email alerts
|

PMU based adaptive zone settings of distance relays for protection of multi-terminal transmission lines

Abstract: This paper proposes Phasor Measurement Unit (PMU) based adaptive zone settings of distance relays (PAZSD) methodology for protection of multi-terminal transmission lines (MTL). The PAZSD methodology employs current coefficients to adjust the zone settings of the relays during infeed situation. These coefficients are calculated in phasor data concentrator (PDC) at system protection center (SPC) using the current phasors obtained from PMUs. The functioning of the distance relays during infeed condition with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[26] analyzes the time differences between the wave travelling from the connection point to the three terminals and the wave from the fault point to the three terminals. Based on this relationship, the fault branch is determined, and then the fault distance between the fault point and the three terminals is calculated [27]. The above methods are all based on the multiterminal data, which require high accuracy of communication, and GPS time sampling [28][29][30].…”
Section: Of 22mentioning
confidence: 99%
“…[26] analyzes the time differences between the wave travelling from the connection point to the three terminals and the wave from the fault point to the three terminals. Based on this relationship, the fault branch is determined, and then the fault distance between the fault point and the three terminals is calculated [27]. The above methods are all based on the multiterminal data, which require high accuracy of communication, and GPS time sampling [28][29][30].…”
Section: Of 22mentioning
confidence: 99%
“…The PMU usage increased in 2004 when the U.S.-Canada investigation report of the 2003 blackout was released. The blackout report recognized that many of North America's major blackouts have been caused by inadequate situational awareness for grid operators and recommended the use of synchrophasor technology to provide real-time wide-area grid visibility [15], [16]. It was demonstrated that new technology and investment was needed to provide adequate situational awareness and the ability to react to such a major disturbance.…”
Section: Synchrophasor Data Description a Related Work Of Synchmentioning
confidence: 99%
“…Considering the investment savings and technical benefits over double-ended systems, multi-terminal transmission systems such as interconnected systems and teed connection transmission lines are increasingly performing in high voltage (HV) and ultra-high voltage power networks [1,2]. However, the protection of such multi-terminal transmission systems is more complex compared to double-ended systems [3]. The problem is that many subsystems and fault locations are relatively dispersed.…”
Section: Introductionmentioning
confidence: 99%